2011
DOI: 10.1002/wrna.104
|View full text |Cite
|
Sign up to set email alerts
|

RNA dynamics: perspectives from spin labels

Abstract: Dynamics are an important and indispensible physical attribute that plays essential roles in RNA function. RNA dynamics are complex, spanning vast timescales and encompassing large number of physical modes. The technique of site-directed spin labeling (SDSL), which derives information on local structural and dynamic features of a macromolecule by monitoring a chemically stable nitroxide radical using electron paramagnetic resonance (EPR) spectroscopy, has been applied to monitor intrinsic dynamics at defined s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
36
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 54 publications
(36 citation statements)
references
References 74 publications
0
36
0
Order By: Relevance
“…Several methods have been developed to attach a paramagnetic tag to nucleic acids (Keyes & Bobst, 2002;Nguyen & Qin, 2012;Qin & Dieckmann, 2004;Shelke & Sigurdsson, 2012): these include replacing structural Mg 2+ with paramagnetic Mn 2+ (Bonneau & Legault, 2014;Kisseleva, Khvorova, Westhof, & Schiemann, 2005), attaching paramagnetic groups to 2 0 -amino modified nucleotides or 4-thiouridines (Piton et al, 2007;Qin, Feigon, & Hubbell, 2005), and the use of paramagnetic phosphoramidites during RNA synthesis (Wunderlich et al, 2013). In the case of large RNAs, annealing and ligating short spin-labeled oligonucleotides to a larger RNA scaffold (Helmling et al, 2014), and enzymatically, using T7 RNA polymerase (Lebars et al, 2014) have been reported.…”
Section: Spin Labeling Of Protein-rna Complexesmentioning
confidence: 99%
“…Several methods have been developed to attach a paramagnetic tag to nucleic acids (Keyes & Bobst, 2002;Nguyen & Qin, 2012;Qin & Dieckmann, 2004;Shelke & Sigurdsson, 2012): these include replacing structural Mg 2+ with paramagnetic Mn 2+ (Bonneau & Legault, 2014;Kisseleva, Khvorova, Westhof, & Schiemann, 2005), attaching paramagnetic groups to 2 0 -amino modified nucleotides or 4-thiouridines (Piton et al, 2007;Qin, Feigon, & Hubbell, 2005), and the use of paramagnetic phosphoramidites during RNA synthesis (Wunderlich et al, 2013). In the case of large RNAs, annealing and ligating short spin-labeled oligonucleotides to a larger RNA scaffold (Helmling et al, 2014), and enzymatically, using T7 RNA polymerase (Lebars et al, 2014) have been reported.…”
Section: Spin Labeling Of Protein-rna Complexesmentioning
confidence: 99%
“…Techniques including NMR and EPR relaxation have been developed to incisively probe motions in the ensemble on different time scales, ranging from picoseconds to milliseconds (3,4). Nonetheless, such dynamic information represents an average of the dynamics of the molecules across the conformational ensemble.…”
Section: Helix-junction-helix | Saxsmentioning
confidence: 99%
“…Over the last decade PDS has been widely used to determine distances within doubly labeled oligonucleotide molecules in the range of 1.5-8 nm (8)(9)(10)(11)(12)(13)(14)(15)(16)(17)(18)(19)(20)(21)(22)(23). Further developments in PDS methods (3) enable even greater distances to be measured.…”
Section: Introductionmentioning
confidence: 98%